Prevalence of Primary Infertility in Iranian Men; a Systematic Review - Moein, Mohammad Reza; Shojaeefar, Ehsan; Taghizabet, Neda; Jazayeri, Maryam; Abbasi Fashami, Mahta; Aliakbari, Fereshteh; Hosseinee, Jalil (Archives of Men’s Health, 2021)
Introduction: Primary infertility (PI) is one of the most common problems with an increasing incidence globally. Studies conducted in several parts of Iran have reported different a prevalence for this infertility type, so we investigated PI prevalence in the Iranian male population. Material and methods: This study was performed using the keywords "primary", "infertility", "prevalence", "men", "male", and "Iran" in international databases, including MedLine, Scopus, Web of Science, ProQuest, as well as domestic databases, including scientific information database (SID) and Magiran. We included original articles estimating PI prevalence and the cause of infertility in the general population and infertile Iranian couples referred to infertility centers. PI prevalence in men was not reported in any included studies, so using weighting based on sample size, the average PI prevalence in the studied couples and any male factors ("male" factors plus "both" factors) was estimated. Results: Thirty-two studies were obtained in the initial search. Ultimately, seven studies (five studies on infertile couples and two studies on the general population) were selected. The weighted average prevalence of PI was 81.26% (81.1-81.43) in referred infertile couples and 5.76% (5.63-5.89) in the general population. The overall estimate of PI prevalence in these groups was 46.35% (46.15-46.54) and 1.93% (1.89-1.97), respectively. Conclusion: Although the PI prevalence in different parts of Iran has been reported in the mentioned population, there was no domestic study on PI prevalence in men, so further studies to validate our results are needed.